Faces do sem nome: o imaginário de Deus em poemas malditos, gozosos e devotos, de Hilda Hilst - Coelho, Kamilla Kristina Sousa França (2010)
This study aims to reflect on the religious images in the poetry of Hilda Hilst (1930-2004). Assisted by some research and studies of Hilst s work, we will analyze poems whose subject is the search for God and the author s desire to understand the divine figure. These are characteristics that underlie the entire poet s work and, in particular, Poemas malditos, gozosos e devotos. We will relate when it is possible the themes and images of the poems that we analyzed to other Hilst s works, because we believe that this action clarifies and enriches the understanding of the divine figure characterized by her. Thus, we can see how the images constructed by the writer reveal a God that configures a universal archetype present in our collective unconscious. As an evidence of the presence of this archetype God and its characteristics in a universal culture, we will cover the Greek mythology, Christianism, the Indians religion, Buddhism, Judaism, Hinduism and Islamism. Furthermore, we will try to understand the archetype of religious with the help of the theories of the imaginary from Gilbert Durand, Maria Zaíra Turchi, Gaston Bachelard and Northrop Frye. To understand the archetypes and the collective unconscious better, we will follow the theories of Carl Gustav Jung. Concerning the religious diversity, we will use the history of Mircea Eliade. To study the religious theme in the Hilst s work, surrounded by the theory of the imaginary, is justified by the cultural and anthropologic contribution that this theory has, what improved our analysis and made possible to have a more comprehensive vision.